Distribution of stem-end rot on the canopy in ‘Hass’ avocado trees in two coastal areas in Peru - Llanos Melo, Alejandro Kepler (2021)
Stem-end rot (SER) of avocado is caused by several fungal species, and it is presented worldwide. This plant disease currently affects several avocado producer regions in Peru, causing fruit rot, impacting the industry negatively. Research about SER distribution in the canopy of avocado trees is limited. Thus, the present study aimed to compare which areas in the canopy are prone to have more SER in ‘Hass’ avocado harvested fruit in two different coastal areas in Peru. The experiment was conducted in the northern (Barranca) and southern (Cañete) of Lima. ‘Hass’Avocado fruits from both producer areas were collected to identify the causal agent; Lasiodiplodia theobromae was isolated from infected fruits. Identification was conducted based on morphological features and a partial DNA sequence of the translation elongation factor 1-α gene (tef1-α). The results showed that fruits inside the tree canopy were prone to have a higher disease incidence than the fruits located in the external site (P<0.001). Besides, internal-site fruits displayed a higher percentage of infected fruit for each grade disease (P<0.001) than external-site fruits, except for grade 0 (fruits without symptoms) and grade 1. Finally, the results suggested that the altitude where the fruit is positioned on the canopy could influence the incidence of SER, where fruits located in the high part revealed less incidence than the low section. The results are valuable for enhancing management strategies and avoiding postharvest loss of avocado fruits in our region.